KERUSAKAN LAHAN AKIBAT KEGIATAN PENAMBANGAN EMAS TANPA IZIN DISEKITAR SUNGAI SINGINGI KABUPATEN KUANTAN SINGINGI - Mailendra, Mailendra; Buchori, Imam (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
Indonesia is one of the countries that has the potential of natural resources other than agriculture, namely mining, especially gold. Gold mining without permits is one of the mining activities which results in a decrease in the quality of the surrounding environment, especially land. The purpose of this study was to look at the land damage that occurred as a result of unlicensed gold mining activities around the Singingi River in the massive Kuantan Singingi Regency in the past two decades. The method used in the analysis is the scoring and overlay method, the data used are Landsat 5 TM and Landsat 8 OLI which are processed using the supervised cllasification method and digitized on screen. Furthermore, as comparative data, surveys and interviews are carried out and utilizing high resolution image data from SPOT images and google earth. The results of this study were found that there was a change in land use from other land uses into unlicensed gold mining land covering an area of 2,680.03 Ha from 2006 to 2018. Then a land damage map with three parameters was produced, namely vegetation density, mine life and type of tailings . Land with a high level of damage covering 699.34 ha, moderate damage 1,501.04 and low damage 479.65. The largest area of land damage occurs in Sungai Paku Village and the smallest village is Pulau Padang.